KONTRIBUSI DAYA LEDAK OTOT TUNGKAI TERHADAP KEMAMPUAN MENENDANG BOLA PEMAIN SEPAKBOLA SPORT SCIENCE FC - Bahtiar Bahtiar; Abdul Rahman; Sulaeman Sulaeman (Program Studi Ilmu Keolahragaan FIK UNM, 2023)
The purpose of this research is to find out; To find out whether there is a contribution in ankle coordination and leg length to the ability to dribble in sport science FC soccer players. The population in this study were all sport science FC soccer players. With a total of 30 people using the total sampling technique. Data collection techniques through passing and stopping tests, anthropometry measurement tests and ball dribbling tests. While data analysis using SPSS version 20 by using descriptive test, normality test and regression test. Based on the results of the statistical analysis, the following conclusions can be drawn: (1) There is a significant contribution between ankle coordination on the ability to dribble in Sport Science FC football players. With an R Square value of 0.227. This means that eye-foot coordination contributes 22.7% to the ability to dribble in Sport Science FC soccer players. (2) There is a significant contribution of leg length to the ability to dribble in Sport Science FC soccer players. With an R Square value of 0.249. This means that leg length contributes 24.9% to the ability to dribble in Sport Science FC soccer players. (3) There is a significant contribution together of ankle coordination and leg length on the ability to dribble in Sport Science FC soccer players. With an R Square value of 0.472. This means that eye-toe coordination and leg length contribute 47.2% to the ability to dribble in Sport Science FC soccer players